Introduction to food biotechnology - Skariyachan, Sinosh (CBS, 2012)
This is a comprehensive book the contents of which have been designed keeping in mind the courses in food biotechnology for the students pursuing undergraduate and postgraduate courses in life sciences and chemical engineering. It can be used as a self-study book for chemical engineers and biological scientists who have limited background in food processing and technology. The book focuses on application of concepts in chemical engineering and biological sciences in the field of food science and technology. Initial chapters emphasize more on the concepts and applications of biological sciences in food industry and the latter section concentrates on the utility of chemical engineering in food technology. It will be a useful guide for biologists and a quick reference for engineers on the latest topics in food science and technology including food biochemistry food microbiology food processing production and preservation technologies food quality assurance and standards and role of biotechnology in food industry. It will also serve as a useful reference for the professionals in food and related industries as well as the teachers handling food processing and technology related courses at the BE/B.Tech or MSc / M.Tech levels